The Advancement Of Energy Harvesting From Road Pavements A Systematic Literature Review - Ng, Lit Phin (Universiti Sains Malaysia, 2022)
Energy harvesting from road pavements is gaining attention worldwide to reduce dependence on non-renewable resources. This technology can harvest wasted energy from vehicle vibrations and solar energy from the sun against road pavement surface layers. This method of energy harvesting has been used on a certain scale as an alternative to the main energy source. This results from the manipulation of small changes in temperature gradients, vibrations from vehicles, and the scattering of sunlight against the pavement surface layer. To determine the selection of an effective road pavement energy harvesting system, criteria such as efficiency, support system, and cost-effectiveness must be taken into account, studied, and analyzed accurately. The main goal of this systematic literature review (SLR) is to provide information to readers and researchers regarding road pavement energy harvesting systems in terms of materials used, mechanisms, technological readiness levels, and cost efficiency. This SLR was conducted according to the preferred reporting method for systematic reviews and meta-analyses (PRISMA) to avoid biased results and increase the validity of the extracted and synthesized data. Cross-references link a total of 35 publications contained in this SLR to further additional sources. A systematic search strategy was used to screen out irrelevant articles and article quality assessment was also applied to avoid publications of poor methodological quality. This SLR is conducted based on findings from studies from the last 10 years (2013-2022) in the field of asphalt technology. It can be used as a guide for researchers in maximizing the potential of energy harvesting systems from road pavements.